ChemInform Abstract: N‐Vinyl‐2‐(trifluoroacetylethynyl)pyrroles and E‐2‐(1‐Bromo‐2‐trifluoroacetylethenyl)pyrroles: Cross‐Coupling vs. Addition During C—H‐Functionalization of Pyrroles with Bromotrifluoroacetylacetylene in Solid Al2O3 Medium. H‐Bonding Control. Issue 39 (8th September 2016) - Tomilin, Denis N.; Gotsko, Maxim D.; Sobenina, Lyubov N.; Ushakov, Igor A.; Afonin, Andrey V.; Soshnikov, Dmitri Yu.; Trofimov, Alexander B.; Koldobsky, Andrey B.; Trofimov, Boris A.
Abstract: Depending on the substituent character at the nitrogen atom, pyrroles react acetylene (II) in two different directions.